The Active Role of Teachers: Building the Foundation of Character Education Through Elementary School - Slamet Riyadi; Siti Sa’idah; Muh. Safar; Meylia Sari; Arifin Arifin (Jurnal Scientia, 2023)
This study investigates the active involvement of elementary school teachers in laying the foundation for character education. Character education is essential for shaping the newer generation's moral, ethical, and responsible personalities. Primary school, as the first level of education, plays a crucial role in molding the character of children. Teachers serve as role models for their students by inspiriting, guiding, and assisting them to realize their highest character potential. The purpose of this study is to provide an in-depth understanding of the active role of teachers in shaping students' character in elementary schools, including the ways in which teachers engage in character education, the strategies they employ, and the challenges they encounter. The study also intends to assess the efficacy of character education implemented by instructors in shaping the character of students. The results demonstrate that instructors play a crucial role in shaping the character of their students. The implementation of character education in elementary schools requires a concerted and persistent effort to create a learning environment that supports and inspires the development of good character.